Selective cyclooxygenase-2 inhibition prevents bone resorption Inibidor seletivo de cicloxigenase-2 prevenindo reabsorção óssea - Carlos Augusto Nassar; Patrícia Oehlmeyer Nassar; Patrícia Maria Nassar; Luis Carlos Spolidorio (Brazilian Oral Research, 2005)
The aim of the present work was to evaluate the effect of a selective cyclooxygenase-2 (COX-2) inhibitor (meloxicam) on the alveolar bone loss progression in experimentally induced periodontitis. Forty (40) Wistar rats were separated into 8 experimental groups (n = 5). Cotton ligatures were placed at the gingival margin level of the lower right first molars of some rats. Four groups were treated for 5 or 15 days with an oral dose of 15 mg/kg of body weight/day of the selective COX-2 inhibitor. The other groups were used as positive control (sham) or negative control in each experimental period. Standardized digital radiographs were taken after sacrifice at 5 and 15 days to measure the amount of bone loss at the mesial root surface of the first molar tooth in each rat. The treatment with meloxicam did not induce weight alteration or other visible systemic manifestations. One way analysis of variance (ANOVA) indicated that groups treated with meloxicam, after 5 days, had significantly less alveolar bone loss (p < 0.05) when compared with control groups. On the other hand, no significant differences in bone loss were observed after 15 days of treatment with meloxicam. These data provide evidence that systemic therapy with meloxicam can modify the progression of experimentally induced periodontitis in rats during the initial experimental period. O objetivo deste trabalho foi avaliar o efeito de um inibidor seletivo da cicloxigenase-2 (COX-2) (meloxicam) na progressão da perda óssea alveolar durante o desenvolvimento da doença periodontal experimental induzida. Quarenta (40) ratos Wistar foram separados em 8 grupos experimentais (n = 5). Ligaduras de fio de algodão foram colocadas na margem gengival do primeiro molar inferior direito de alguns ratos. Quatro grupos foram tratados por 5 ou 15 dias com uma dose oral de 15 mg/kg de peso corporal/dia do inibidor seletivo de COX-2. Os outros grupos foram usados como controle positivo (sham) e controle negativo dentro de cada período experimental. Radiografias digitais padronizadas foram realizadas para medir a perda óssea na região mesial do primeiro molar inferior de cada rato. O efeito do tratamento com meloxicam não induziu alteração de peso ou outras manifestações sistêmicas visíveis. A Análise de Variância (ANOVA) indicou que os grupos tratados com meloxicam após 5 dias apresentaram perda óssea alveolar significativamente menor (p < 0,05). Por outro lado, a perda óssea não foi significativa após 15 dias de tratamento com meloxicam. Os dados apresentados no presente trabalho sugerem que o tratamento sistêmico com meloxicam pode modificar a progressão da periodontite experimental em ratos no período experimental inicial.